Penerapan Model PBL Melalui Pendekatan CRT untuk Meningkatkan Hasil Belajar Matematika Kelas 1 di SDN Putat Jaya IV-380 Surabaya - Karenina Ade Hidayah; Desi Eka Pratiwi; Herlia Nimas Ayu Hastungkoro (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research is motivated by the low learning outcomes of first-grade students in the subject of mathematics, specifically in the topic of grouping and presenting data in the form of lists and tables. The aim of this study is to investigate the improvement of first-grade students' learning outcomes in mathematics through the implementation of the problem-based learning model using a culturally responsive teaching approach. This research is classified as a classroom action research conducted in two cycles. The subjects of this study are 27 first-grade students from SDN Putat Jaya IV-380 Surabaya. Data for this research were collected through observations and tests, and were analyzed using quantitative descriptive methods. The results indicate that implementing problem-based learning through a culturally responsive teaching approach can enhance students' learning outcomes in mathematics, specifically in the topic of grouping and presenting data in the form of lists and tables. The average pre-cycle learning outcome was 69.55, which increased to 78.51 after the first cycle of PBL implementation, and further improved to 90.88 in the second cycle. Based on these findings, it can be concluded that the problem-based learning model through culturally responsive teaching is effective in enhancing the learning outcomes of first-grade students in mathematics at SDN Putat Jaya IV-380 Surabaya..